Evaluasi Rasionalitas Penggunaan Antibiotik Pada Pasien dengan Demam Tifoid di Rumah Sakit X di Surakarta - Adhi W. Amrullah; Rolando Rahardjoputro; Atiek Murharyati; Avianti Eka Dewi Aditya Purwaningsih (Jurnal Farmasi Indonesia, 2024)
The bacterium Salmonella typhi is the cause of a systemic infection known as typhoid fever. These bacteria usually enter through contaminated food or drink. To treat typhoid fever, antibiotics must be given as rationally as possible to achieve ideal therapeutic goals. An understanding of various aspects of an infectious disease should be used to plan the use of antibiotics. This understanding must also consider the pharmacokinetics and pharmacodynamics of the antibiotic to be used as well as individual resistance, virulence and microorganisms. The development of antibiotic-resistant bacteria is the worst effect of irrational use of antibiotics. In this study, the Gyssens method was used to analyze the rationality of antibiotics. This observational descriptive study also uses a cross-sectional approach. Data was collected through a retrospective search of medical records in the medical records section of "X" Hospital in Surakarta from January to December 2021. The data collected consisted of analytic and descriptive data, which consisted of patient characteristics and the patient's pattern of prescribing antibiotics. The SPSS computer program is used to process the data. The results of rationality analysis showed that in 84 prescriptions in typhoid fever patients who were included in category 0 (zero) or rational as many as 25 prescriptions (29.76%) and irrational as many as 59 prescriptions (70.24%) consisting of category IV A as many as 18 prescriptions (21.43%), IV B as many as 8 prescriptions (9.52%), III A as many as 3 prescriptions (3.57%), category III B as many as 47 prescriptions (55.95%), II A as many as 34 prescriptions (40.47%) and II B as many as 27 prescriptions (32.14%).